ADVANCED EXPERIMENTAL BIFURCATION ANALYSIS: BASELINE SCENARIO OF DYNAMICS EVOLUTION - Kolokolov, Yury V.; Monovskaya, Anna V. (International Journal of Computing, 2015)
The paper develops the advanced experimental bifurcation analysis, where the extended data acquisition, the intelligent data processing, and the modified bifurcation diagrams are combined to get useful information for different specified purposes. In particular, here we focus on how to estimate experimentally the nearest limit of the operating process stability loss without expert opinions. So, we consider the baseline scenario of dynamics evolution, where the peculiarity of the estimation is connected with the possibility to determine the uncertainty zone about the corresponding bifurcation points. The algorithms of both data acquisition and data processing are illustrated. The procedures of the algorithms are founded on the methods of the experimental researches of different nonlinear phenomena under uncertainties. The presented results can be applied to engineering design.